Feature Distribution and Word Order Variation in Arabic Clauses: A Minimalist Account - S. Ellafi , Ali (Scientific Journal of University of Benghazi, 2024)
Arabic subject-verb agreement is asymmetrical: in VSO order the verb agrees with the subject in person and gender (partial agreement), whereas in SVO order the verb exhibits number agreement as well (full agreement). This agreement asymmetry has received a lot of attention in the generative literature over the past three decades. In fact, more than twenty proposals have been put forward in a number of different theoretical frameworks. At the same time, there have been no attempts for a formal treatment of OVS word order constructions. With respect to agreement, the OVS verb exhibits both of the properties that exist in the other word order types (VSO and SVO): partial agreement with the post-verbal subject and full agreement with the pre-verbal DP. A more thorough consideration of the data reveals that pre-verbal DPs share a number of other rather interesting properties. Our empirical findings lead to the conclusion that pre-verbal DPs (i.e., the superficial subject and object of SVO and OVS, respectively) are actually topics. The real subject of SVO and, similarly, the object of OVS is in fact verbally bound pronominal clitics. Using a Merge, Move and Agree-based theory of phrase structure and feature checking; and a Multiple Spell-Out model of phasal derivation, we hope to demonstrate that the computational systems of Minimalist Syntax can provide an adequate treatment of seven constructions: VSO, SVO and OVS, as well as four related variants (Ɂinna-headed SVO and OVS, and pro-drop SVO and OVS).